2021
DOI: 10.1155/2021/4848483
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on Ultimate Shear Load Carrying Capacity of Corroded RC Beams

Abstract: For an RC beam, the strength of steel rebar, the bonding strength between the concrete and reinforcement, and the bite action between the aggregates will deteriorate significantly due to corrosion. In the present study, 10 RC beams were designed to study the impact of corrosion on the shear bearing capacity. The mechanism of corrosion for stirrups and longitudinal bars and their effects were analyzed. Based on the existing experimental data, the correlation between the stirrup corrosion factor and the cross se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…In order to obtain a comprehensive assessment of the seismic behavior of reinforced concrete structures, this study specifically focuses on the effect of two different types of stirrups, i.e., hooked and unhooked stirrups. Previous research has shown that hooked stirrups can improve energy dissipation and ductility by providing additional restraint to the concrete core, while unhooked stirrups, although widely used, may provide relatively limited benefits in this regard [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Rosso et al [19] estimated the effect of corrosion on the capacity and ductility in their study.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain a comprehensive assessment of the seismic behavior of reinforced concrete structures, this study specifically focuses on the effect of two different types of stirrups, i.e., hooked and unhooked stirrups. Previous research has shown that hooked stirrups can improve energy dissipation and ductility by providing additional restraint to the concrete core, while unhooked stirrups, although widely used, may provide relatively limited benefits in this regard [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Rosso et al [19] estimated the effect of corrosion on the capacity and ductility in their study.…”
Section: Introductionmentioning
confidence: 99%